The role of economics in forest planning and policy evaluation in Slovenia - Hodges, Donald G. (Acta silvae et ligni, 2014)
This paper explores the current status of the forest sectors in Slovenia, identifies potential issues in the management and use of the forests, and discusses a means by which policy makers can identify opportunities to enhance the role played by forests and their related goods and services in Slovenia. Specifically, a framework is proposed to assess the relationships between the economic, social, and ecological aspects of Slovenia%s forests; effects of changes in economic conditions on forest demands and uses; economic impacts of ecological, social, and business conditions; effects of current or proposed policies; and opportunities for the sustainable economic development of wood-based and forest-dependent enterprises. Such a framework is critical for managing Slovenia's forests and forestry sector in such a manner to optimize the ecological and economic potential.
Keywords: ekonomski učinki; pametna specializacija; lesna proizvodnja; papirna proizvodnja; ekosistemske storitve